2016
DOI: 10.1111/head.12742
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Features of a Probable Diagnosis in First‐Visit Headache Patients Based on the Criteria of the Third Beta Edition of the International Classification of Headache Disorders: A Prospective, Cross‐Sectional Multicenter Study

Abstract: A probable diagnosis was given to 21.3% of the first-visit PHD patients due to incomplete or atypical presentations of the headaches. The incorporation of a probable diagnosis into the ICHD-3β may be useful for reducing the diagnoses of unspecified headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A previous multicenter, cross-sectional registry study found that a diagnosis of probable primary headache disorder, based on ICHD-3β, was given to 21.3% of first-visit patients due to incomplete or atypical presentations of the headaches. The proportions of probable primary headache disorders differed among the subtypes as follows: migraines (16.1%), tension-type headaches (33%), TACs (40.9%), and other primary headache disorders (14%) ( 12 ). Although a difference is noticeable, it is difficult to make a direct comparison because the number of patients included and the method of investigation used differed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous multicenter, cross-sectional registry study found that a diagnosis of probable primary headache disorder, based on ICHD-3β, was given to 21.3% of first-visit patients due to incomplete or atypical presentations of the headaches. The proportions of probable primary headache disorders differed among the subtypes as follows: migraines (16.1%), tension-type headaches (33%), TACs (40.9%), and other primary headache disorders (14%) ( 12 ). Although a difference is noticeable, it is difficult to make a direct comparison because the number of patients included and the method of investigation used differed.…”
Section: Discussionmentioning
confidence: 99%
“…According to two population-based surveys, the most common unmet criterion preventing a definitive migraine diagnosis was headache duration (61.1 and 82.0%, respectively); a separate multicenter study identified the number of attacks (41.9%) and associated symptoms (33%) as the most common unmet symptoms ( 6 , 10 , 12 ). Number of attacks (65.3%) was also the most commonly unmet criterion among cases of probable tension-type headache ( 12 ). In terms of unmet criteria, the prevalence of diagnostic stability was lower in subgroups lacking data on time-based criteria, such as number of attacks or total headache period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation was based on the Headache Registry using ICHD-3β for First-Visit Patients (HEREIN) study, which is a cross-sectional multicenter registry study that uses data collected from first-visit headache outpatients presenting at neurology clinics in Korea between August 2014 and February 2015. 15 16 17 …”
Section: Methodsmentioning
confidence: 99%
“…This was a substudy of the headache registry using ICHD-3β for the first-visit patients (HEREIN) study using prospectively collected multicenter data obtained from consecutive first-visit headache outpatients in the headache clinics of 11 hospitals in Korea between August 2014 and February 2015 [ 11 13 ]. The study design of the HEREIN study was proposed and reviewed at regular educational meeting of the Korean Headache Society after a request regarding the application of ICHD-3β; study members were board-certified neurologists with special interests in the headache field.…”
Section: Methodsmentioning
confidence: 99%